2005
DOI: 10.1016/j.cub.2004.12.079
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Homeobox Gene STIMPY/WOX9 for Arabidopsis Meristem Growth and Maintenance

Abstract: Most organs of flowering plants develop postembryonically from groups of pluripotent cells called meristems [1]. The shoot apical meristem (SAM) is specified by two complementary pathways [2-4]. SHOOT MERISTEMLESS (STM; [5]) defines the entire SAM region [6]. WUSCHEL (WUS), on the other hand, functions in a more restricted set of cells to promote stem-cell fate and is regulated by the CLAVATA genes in a negative feedback loop [7-10]. In contrast, little is known about how the growth of the SAM, which increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
232
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(260 citation statements)
references
References 34 publications
11
232
0
3
Order By: Relevance
“…WOX9 has been proposed to coordinate cytokinin-and sugar-mediated signaling in shoot meristem development (27)(28)(29). In addition, STF modulation of robust hormone and sugar homeostasis in leaf blade development has been proposed (15).…”
Section: Discussionmentioning
confidence: 99%
“…WOX9 has been proposed to coordinate cytokinin-and sugar-mediated signaling in shoot meristem development (27)(28)(29). In addition, STF modulation of robust hormone and sugar homeostasis in leaf blade development has been proposed (15).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, WUS and WOX5 are involved in the de novo formation of meristems and somatic embryos from differentiated cells (Zuo et al, 2002;Gallois et al, 2004;Gordon et al, 2007;Chen et al, 2009;Sugimoto et al, 2010). Second, two members of the WOX9 clade, WOX8 and WOX9, redundantly regulate zygote development and embryo axis formation (Breuninger et al, 2008;Ueda et al, 2011) and WOX9 has an additional role in shoot meristem regulation (Wu et al, 2005). Finally, recent reports show that members of the WOX13 clade affect replum development, and dehiscence, flowering time, lateral root formation, and fertility (Deveaux et al, 2008;Romera-Branchat et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…4 WOX5 functions in stem cell maintenance 5 and WOX9/ STIMPY acts in early embryonic growth in the root apices. 6 In rice, WOX11 plays an important role in the emergence and growth of adventitious roots, and directly represses the cytokinin type-A responsive regulator RR2, which is expressed in adventitious root primordia. 7 Our recent study demonstrated that OsWOX3A regulates the development of lateral roots, but not adventitious roots.…”
mentioning
confidence: 99%